Double 90 Degrees Counterrotated End-to-End-Anastomosis: An Experimental Study of an Intestinal Anastomosis Technique - Holzner, Philipp; Kulemann, Birte; Seifert, Gabriel; Glatz, Torben; Chikhladze, Sophia; Höppner, Jens; Hopt, Ulrich; Timme, Sylvia; Bronsert, Peter; Sick, Olivia; Zhou, Cheng; Marjanovic, Goran (European Journal of Pediatric Surgery, 2015)
Aim The aim of the article is to investigate a new anastomotic technique compared with standardized intestinal anastomotic procedures.Materials and Methods A total of 32 male Wistar rats were randomized to three groups. In the Experimental Group (n = 10), the new double 90 degrees inversely rotated anastomosis was used, in the End Group (n = 10) a single-layer end-to-end anastomosis, and in the Side Group (n = 12) a single-layer side-to-side anastomosis. All anastomoses were done using interrupted sutures. On postoperative day 4, rats were relaparotomized. Bursting pressure, hydroxyproline concentration, a semiquantitative adhesion score and two histological anastomotic healing scores (mucosal healing according to Chiu and overall anastomotic healing according to Verhofstad) were collected. Most data are presented as median (range). p < 0.05 was considered significant.Results Anastomotic insufficiency occurred only in one rat of the Side Group. Median bursting pressure in the Experimental Group was 105 mm Hg (range = 72–161 mm Hg), significantly higher in the End Group (164 mm Hg; range = 99–210 mm Hg; p = 0.021) and lower in the Side Group by trend (81 mm Hg; range = 59–122 mm Hg; p = 0.093). Hydroxyproline concentration did not differ significantly in between the groups. The adhesion score was 2.5 (range = 1–3) in the Experimental Group, 2 (range = 1–2) in the End Group, but there were significantly more adhesions in the Side Group (range = 3–4); p = 0.020 versus Experimental Group, p < 0.001 versus End Group. The Chiu Score showed the worst mucosal healing in the Experimental Group. The overall Verhofstad Score was significantly worse (mean = 2.032; standard deviation [SD] = 0.842) p = 0.031 and p = 0.002 in the Experimental Group, compared with the Side Group (mean = 1.729; SD = 0.682) and the End Group (mean = 1.571; SD = 0.612).Conclusion The new anastomotic technique is feasible and did not show any relevant complication. Even though it was superior to the side-to-side anastomosis by trend with respect to functional stability, mucosal healing surprisingly showed the worst results. Classical end-to-end anastomosis still seems to be the best choice regarding structural and functional anastomotic stability.
Keywords: anastomosis; bursting pressure; hydroxyproline; ischemia; adhesion